Communication on Early Childhood Education (PAUD) in the State Kinderganden School of Waingapu - Putri Ekaresty Haes; Gede Suardana (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Education is the right of every citizen, including early childhood education (PAUD). The purpose of this study was to describe the implementation of educational communication carried out at the state kindergarden school of Waingapu in shaping the man or woman of youngsters. The sort of qualitative research with a descriptive method turned into chosen to describe the consequences of this take a look at thru observation, interviews, and documentation strategies, while the data validity technique used techniques and sources. The results of this observe screen that the state kindergarten school of Waingapu has implemented educational communication effectively. Not only in classroom learning, but also with parents of students, so that the interaction between educators and external stakeholders becomes effective. In addition, educational communication that has been implemented has been able to shape the character of early childhood, through learning messages given by the educator providing a strong character basis for early childhood so that children can adapt to the environment.